Bed load transport modeling of a secondary flow influenced curved channel with 2D and 3D numerical models. Issue 1 (2nd January 2016) - Riesterer, Jochen; Wenka, Thomas; Brudy-Zippelius, Thomas; Nestmann, Franz
Abstract : Due to the complex physical interactions that affect the flow processes in curved channel sections, measuring and simulating the morphological processes has been the object of scientific studies for quite a long time. The occurring secondary flow exerts a major influence on bed formation and on bed load transport in channel bends. To analyze these effects, numerical simulations of a meandering laboratory channel were performed by means of the open-source Telemac–Sisyphe program system. The study focuses on the importance of two-dimensional (2D) or three-dimensional (3D) approaches for the flow simulation underlying the morphological investigations. Hence, the numerical studies were performed in a 2D and 3D model and the morphological development was analyzed. The differentiated model studies showed local differences in the morphological results as a consequence of the different spatial resolution of flow modeling. The 3D model provided an improved description of the situation observed in the laboratory especially in the regions of development and decay of secondary flow. Regarding the maximum sedimentation and erosion as well as the bed development tendencies within the whole model area, the 2D and 3D model determine the laboratory observations.